1940
DOI: 10.1084/jem.71.1.29
|View full text |Cite
|
Sign up to set email alerts
|

A Crystalline Pressor Substance (Angiotonin) Resulting From the Reaction Between Renin and Renin-Activator

Abstract: 1. Renin reacts with renin-activator to form a strong pressor substance which is heat-stable, water- and alcohol-soluble, fluorescent, acid-stable, and alkali-labile. It is a reducing substance and is destroyed by strong oxidizing substances. It forms crystalline salts with oxalic and picric acids. The color reaction for arginine is the only one found to be strongly positive. It is suggested that this substance be called angiotonin. 2. Angiotonin produces a sharp, immediate rise in arterial pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
95
0
16

Year Published

1941
1941
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(112 citation statements)
references
References 1 publication
1
95
0
16
Order By: Relevance
“…Renin was a central subject of intense investigation because of its role in blood pressure regulation before the discovery of angiotensinogen. Early studies by two groups, led respectively by Page and Braun-Menendez, independently demonstrated that renin was not the direct cause of experimental hypertension, but rather it acted on a substance in plasma to yield a heat-stable peptide possessing both pressor and vasoconstrictor functions [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Renin was a central subject of intense investigation because of its role in blood pressure regulation before the discovery of angiotensinogen. Early studies by two groups, led respectively by Page and Braun-Menendez, independently demonstrated that renin was not the direct cause of experimental hypertension, but rather it acted on a substance in plasma to yield a heat-stable peptide possessing both pressor and vasoconstrictor functions [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotonin, a pressor substance arising out of the reaction between renin and renin-activator, has been suggested by Page and Helmer (1) as the humoral mediator of clinical and experimental hypertension. The vasopressor activity of this substance in animals is not abolished by anesthesia or pithing; it causes vasoconstriction in the isolated rabbit's ear (1) and reduces the renal blood flow by constriction of the efferent glomerular arterioles (2), facts which lead to the belief that it acts directly on the peripheral vascular bed.…”
mentioning
confidence: 99%
“…The vasopressor activity of this substance in animals is not abolished by anesthesia or pithing; it causes vasoconstriction in the isolated rabbit's ear (1) and reduces the renal blood flow by constriction of the efferent glomerular arterioles (2), facts which lead to the belief that it acts directly on the peripheral vascular bed. It is also known that it decreases the diastolic volume in the isolated mammalian heart (3).…”
mentioning
confidence: 99%
“…Whether the sustained hypertension is due to the salt and water retention and increase in plasma volume, or to the reduction in concentration of vasodilator agents, such as bradykinin or prostaglandins, or to the release of vasoconstricting agents other than renin as proposed by Grollman, and KrishmanAmerty* 7 by Skeggs et al M and by Boucher et al' 9 is not yet established. Riegger and the other members of the Glasgow group," however, have proposed that angiotensin II is responsible for the initial rise in systemic pressure and for the sustained hypertension in sodium-replete dogs.…”
mentioning
confidence: 98%